16d+(4+-5d)=-67

Simple and best practice solution for 16d+(4+-5d)=-67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16d+(4+-5d)=-67 equation:


Simplifying
16d + (4 + -5d) = -67

Remove parenthesis around (4 + -5d)
16d + 4 + -5d = -67

Reorder the terms:
4 + 16d + -5d = -67

Combine like terms: 16d + -5d = 11d
4 + 11d = -67

Solving
4 + 11d = -67

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 11d = -67 + -4

Combine like terms: 4 + -4 = 0
0 + 11d = -67 + -4
11d = -67 + -4

Combine like terms: -67 + -4 = -71
11d = -71

Divide each side by '11'.
d = -6.454545455

Simplifying
d = -6.454545455

See similar equations:

| x^2-3x+63=0 | | 3x+(-8)=1 | | 5ln(y)-5ln(y+0.2)= | | 5ln(y)-5ln(y+0.2)=ln(x) | | W(l-4)=96 | | x^4-x+14.7=0 | | G(-x)=2x^2+7x-7 | | 7(4)-2(4)= | | 2a/3a÷3a/2b | | -6=2/7m | | 25-3x^2/4 | | 180=(2x-25)+(5x+30) | | a/14 | | 12=-4/5y | | (x-3-5i)(x-3-5i)=0 | | 5x-7=8x-11 | | X=.60x+.40x | | p^2+2pq-35q^2=0 | | 6x^2+11x-7=(2x-1)w | | 9x-4=32+2x | | 3c=12d-15 | | 20=5c-5d | | x/120=65/100 | | f(x)=x^2-5x+2ix-5x-2ix+25-10i+10i-4i^2 | | x+0.05x=1621.94 | | x+1=5x+12 | | A*14=6.8 | | 4x+1y=588 | | 2*5w=40 | | y=1.2x+6 | | 4x+92=2-6x | | 4x+2=9x+32 |

Equations solver categories